THE USE OF VISUAL CARD MEDIA IN TEACHING LEARNING GRAMMAR AT THE SECOND GRADE OF MADRASAH ALIYAH NEGERI (MAN) PAMEKASAN - Solichin, Mohammad Muchlis; Faizin, Akhmad (OKARA: Jurnal Bahasa dan Sastra, 2017)
This research wants to know 1) How does the teacher implement visual card media on students grammar at the second grade of MAN Pamekasan? 2. What are the problems faced by the students in teaching grammar by using visual card media on students grammar at the second grade of MAN Pamekasan 3. How does the student’s response to the implementation of visual card media on students’ grammar at the second grade of MAN Pamekasan. The researcher uses the qualitative approach, that has become because it provides valuable insights into the local perspectives of study population, and chooses to use non- participant observation, The finding of the research are: 1) The implementation of visual card media in teaching grammar at the second grade of MAN Pamekasan is very good. It makes students active in the class and enjoys in the learning process. 2) the student’s problems in the implementation of visual card media in teaching grammar at the second grade of MAN Pamekasan are the preparation of students, less comprehension, self-confidence. 3. The student’s give the positive response.